Uptake and Catabolism of 125l-Thrombin by the Rabbit Thoracic Aorta In Vitro: Permeability of the Endothelium, Intima-Media and Adventitial Layers - Hatton, Mark W C; Moar, Sue L (Thrombosis and Haemostasis, 1984)
The uptake, distribution and catabolism of 125I-thrombin has been studied in vitro using normal and ballooned (de-endothelialized) aorta segments at 37° C and at 4° C. In addition to rapid uptake by endothelial cells, 125I-thrombin passed at a slower, and yet constant, rate through the endothelium and accumulated in the intima-medial and adventitial layers. The enzyme, however, was not able to cross the adventitia. Passage through the endothelium was probably intercellular rather than due to transcytosis. Uptake by the intima-media layer of ballooned segments was substantially faster (× 2.5) than by the subendothelial (intima-media) region of normal segments. Once associated with the endothelium and the subendothelial layers, 125I-thrombin was catabolized and radioactive products, which were released from the vessel wall, appeared in the incubation medium. Two possible catabolic routes were identified: 1. the enzyme was recovered as a high molecular weight product (i. e. excluded by Sephadex G-200), due to complex formation with an extracellular vessel wall component and/or plasma antithrombin III. 2. Fragments of the enzyme were recovered which were presumably the products of limited, extracellular proteolysis.
Keywords: Thrombin; Vessel wall permeability; Endothelium; Subendothelium; Aorta; Intima media